Kredibilitas Pemberitaan Distribusi Vaksin Covid-19 di Indonesia - Anisa Suci Rahmawati; Ferry Darmawan (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Since March 2020, news about the Covid-19 pandemic has increasingly dominated media content considering that the virus has begun to enter this country. This study focuses on media coverage of the distribution of the Covid-19 vaccine. The purpose of this study is to determine the credibility (accuracy, believability, bias and completeness) online media Detik.com and Kompas.com. This study uses a quantitative approach with content analysis method. Data collection techniques are carried out by the coding process statements or writing. Flanagin and Metzger's credibility theory was used with the object of research being the credibility of the Covid-19 vaccine distribution news in the online media Detik.com and Kompas.com December 2020 - February 2021 edition. The results of the study stated that the news published by Kompas.com on the believability dimension received 21% opinion and 93% transparency. Dimension accuracy is 100% according to the title, 73% there is a writing error, and 43% is the suitability of the photo. The bias dimension is 53% cover both sides and the completeness dimension is 80% completeness 5W+1H. For news published by Detik.com on the believability dimension, it gets 18% opinion and 87% transparency. Dimension accuracy is 100% according to the title, 47% there are writing errors, and 88% is the suitability of the photo. The bias dimension is 33% cover both sides and the completeness dimension is 100% completeness 5W+1H. Based on the four dimensions, news about the distribution of the Covid-19 vaccine in Indonesia published by Kompas.com and Detik.com did not all meet the dimensions of credibility. Abstrak. Semenjak bulan Maret 2020 pemberitaan seputar pandemi Covid-19 semakin mendominasi isi media mengingat virus tersebut mulai memasuki negeri ini. Penelitian ini berfokus pada pemberitaan media mengenai distribusi vaksin Covid-19. Tujuan penelitian ini adalah untuk mengetahui kredibilitas (accuracy, believability, bias dan completeness) media online Detik.com dan Kompas.com. Penelitian ini menggunakan pendekatan kuantitatif dengan metode analisis isi. Teknik pengumpulan data dilakukan dengan cara proses coding atau menyandi pernyataan atau penulisan. Untuk membedah penelitian ini digunakan teori kredibilitas Flanagin dan Metzger dengan objek penelitian kredibilitas pemberitaan distribusi vaksin Covid-19 di media online Detik.com dan Kompas.com edisi Desember 2020 – Februari 2021. Hasil penelitian menyatakan berita yang dimuat Kompas.com pada dimensi believability mendapatkan 21% opinitative dan 93% transparansi. Dimensi accuracy 100% kesesuaian judul, 73% ada kesalahan penulisan, dan 43% kesesuaian foto. Dimensi bias 53% cover both sides dan dimensi completeness 80% kelengkapan 5W+1H. Untuk berita yang dimuat Detik.com pada dimensi believability mendapatkan 18% opinitative dan 87% transparansi. Dimensi accuracy 100% kesesuaian judul, 47% ada kesalahan penulisan, dan 88% kesesuaian foto. Dimensi bias 33% cover both sides dan dimensi completeness 100% kelengkapan 5W+1H. Berdasarkan keempat dimensi, berita mengenai distribusi vaksin Covid-19 di Indonesia yang dimuat Kompas.com dan Detik.com belum semua memenuhi dimensi dalam kredibilitas.